2013
DOI: 10.1371/journal.pone.0069695
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Parental Influences on Offspring Health and Growth in Great Tits (Parus major)

Abstract: Sexual selection requires both that there is heritable variation in traits related to fitness, and that either some of this variation is linked to traits of the parents, and/or that there are direct benefits of choosing particular individuals as mates. This suggests that if direct benefits are important offspring performance should be predicted by traits of the rearing adults. But if indirect benefits are more significant offspring performance should be predicted by traits of the adults at the nest-of-origin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Because of these different sources of selection, similar ornaments expressed in both sexes could relate to different aspects of quality, though only a few recent studies have found such differences (Kelly et al, 2012;Pickett et al, 2013). Here, we demonstrate that plumage coloration in female and social male tree swallows is similarly related to nestling immunity, while different aspects of coloration are related to bactericidal capacity in adults.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Because of these different sources of selection, similar ornaments expressed in both sexes could relate to different aspects of quality, though only a few recent studies have found such differences (Kelly et al, 2012;Pickett et al, 2013). Here, we demonstrate that plumage coloration in female and social male tree swallows is similarly related to nestling immunity, while different aspects of coloration are related to bactericidal capacity in adults.…”
Section: Discussionmentioning
confidence: 55%
“…Female ornamentation is more likely maintained by social selection, competition among conspecific females for resources other than mates (LeBas, 2006;Tobias et al, 2012). Because different selective pressures maintain ornamentation in each sex, it is possible that similar ornaments are related to different aspects of individual and/or offspring quality in each sex (Massaro et al, 2003;Kekäläinen et al, 2010;Kelly et al, 2012;Pickett et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the blue‐footed booby ( Sula nebouxii ), Velando, Torres, and Espinosa () found no correlation between nestling PHA and father's foot colouration, whereas in great tits, Pickett et al. () found a positive correlation between nestlings’ PHA and genetic father's but not mother's yellow plumage brightness. In the same species, Remeš and Matysioková () found that females with more immaculate white cheeks produce offspring with a higher PHA.…”
Section: Introductionmentioning
confidence: 99%
“…In great tits (Parus major) for example, such experiments have provided support for direct and indirect benefits of carotenoid and melanin-based colouration in males and females. Indeed, great tits with a larger black breast stripe were found to produce more viable or heavier young (Norris, 1993;Remeš & Matysioková, 2013), whereas yellower males and females with a blacker breast stripe were found to raise heavier nestlings (Pickett, Weber, Mcgraw, Norris, & Evans, 2013).…”
Section: Introductionmentioning
confidence: 99%